Effect of addition of different hydrocolloids on pasting, thermal, and rheological properties of cassava starch - Leite,Tatiana Dias (2012)
Starches and gums are hydrocolloids frequently used in food systems to provide proper texture, moisture, and water mobility. Starch-gum interaction in food systems can change the starch granule swelling and its gelatinization and rheological properties. In this study, the effect of the addition of xanthan gum (XG), sodium carboxymethyl cellulose (SCMC), and carrageenan (CAR) at the concentrations of the 0.15, 0.25, 0.35 and 0.45% (w/v) on the pasting, thermal, and rheological properties of cassava starch was studied. The swelling power (SP) and the scanning electron microscopy (SEM) of the starch gels were also evaluated. The results obtained showed that xanthan gum (XG) had a strong interaction with the cassava starch penetrating between starch granules causing increase in pasting viscosities, SP, storage and loss (G', and G", respectively) modulus and reduction in the setback of the starch; sodium carboxymethyl cellulose (SCMC) greatly increased the pasting viscosities, the SP, and the storage and loss (G', and G", respectively) modulus of the starch-mixtures, mainly due to its greater capacity to hold water and not due to the interaction with cassava starch. Carrageenan (CAR) did not change any of the starch properties since there was no interaction between this gum and cassava starch at the concentrations used.